Interactive Multimedia Introduction To 3D Animation-Based Body Management Procedures For Muhammadiyah 1 Elementary School Students Bengkulu City - Heru Franata; Eka Sahputra; Ardi Wijaya; Marhalim Marhalim (Jurnal Komputer, Informasi dan Teknologi, 2023)
This research was conducted in order to be able to further assist teachers in providing material related to procedures for managing corpses based on 3D animation. In this study the authors used empirical methods, in which data collection was carried out in several steps, namely: Observation and Library Studies. In addition, the system design has 2 (two), namely: First Marker Check (Washing the Body) and Initialization. Then there are 4 (four) paths in application design, namely: Interface Design, Splashscreen Menu, Main Menu, Prayer Movement AR Menu. And the last one is testing, where testing of the process book augmented reality application for children is carried out. Before the application is tested on users, it is first carried out using the white box testing method, testing the application on devices with the Android operating system. From this study it can be concluded that the stages involved in developing a 3D multimedia in the form of augmented reality consist of the process of modeling, texturing, ringing, animation, rendering, making APKs. The results of the animation making process are then arranged in a single unit using vuforia and unity so as to produce a 3D animation-based corpse management movement guide application.